2003
DOI: 10.1086/367783
|View full text |Cite
|
Sign up to set email alerts
|

Galactic Bulges from [ITAL]Hubble Space Telescope[/ITAL] Near-Infrared Camera Multi-Object Spectrometer Observations: The Lack of [CLC][ITAL]r[/ITAL][/CLC][TSUP]1/4[/TSUP] Bulges

Abstract: We use Hubble Space Telescope (HST) near-infrared imaging to explore the shapes of the surface brightness profiles of bulges of S0-Sbc galaxies at high resolution. Modeling extends to the outer bulge via bulge-disk decompositions of combined HST-ground-based profiles. Compact, central unresolved components similar to those reported by others are found in ∼84% of the sample. We also detect a moderate frequency (∼34%) of nuclear components with exponential profiles that may be disks or bars. Adopting the Sérsic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
199
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(217 citation statements)
references
References 39 publications
16
199
2
Order By: Relevance
“…The exact shape of bulge profiles remains under debate (e.g., Balcells et al 2003, and references therein). Locally, there is evidence that the bulges of late-type spiral galaxies may be better fit by an n = 1 profile, whereas bright ellipticals and the bulges of early-type spiral galaxies follow an n = 4 profile (de Jong 1996;Courteau et al 1996;Andredakis 1998).…”
Section: Fitting Modelmentioning
confidence: 99%
“…The exact shape of bulge profiles remains under debate (e.g., Balcells et al 2003, and references therein). Locally, there is evidence that the bulges of late-type spiral galaxies may be better fit by an n = 1 profile, whereas bright ellipticals and the bulges of early-type spiral galaxies follow an n = 4 profile (de Jong 1996;Courteau et al 1996;Andredakis 1998).…”
Section: Fitting Modelmentioning
confidence: 99%
“…Balcells et al (2003) report that early-type disk galaxies tend to have n < 3 and often from 1 to 2. Laurikainen et al (2007) find barred and unbarred early-type disk galaxies to have mean B/T between 0.25 and 0.35, while later Hubble types have B/T < 0.2; they also find mean bulge Sérsic indices to be ∼ 2.5 or less across the Hubble sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Krajnović et al (2008) found NDs in early-type galaxies are associated with fast rotators. Near-infrared Hubble Space Telescope (HST) imaging has also provided indirect evidence for NDs as discy isophotes in the nuclei of early-type galaxies (Ravindranath et al 2001) or photometrically distinct exponential components in bulges (Balcells et al 2003). Erwin et al (2014) also found evidence for NDs which they call "discy pseudobulges".…”
Section: Introductionmentioning
confidence: 99%